Ecosystem functional changes associated with land clearing in NW Argentina - Volante, José Norberto (2012)
We assessed the extension of natural habitat conversion into croplands and grazing lands in subtropical NW Argentina and its impact on two key ecosystem functional attributes. We quantified changes in remotely sensed surrogates of aboveground net primary production (ANPP) and seasonality of carbon gains. Both functional attributes are associated with intermediate ecosystem services sensu Fisher et al. (2009). Deforestation was estimated based on photointerpretation of Landsat imagery. The seasonal dynamics of the MODIS satellite Enhanced Vegetation Index (EVI) was used to calculate the EVI annual mean as a surrogate of ANPP, and the EVI seasonal coefficient of variation as an indicator of seasonal variability of carbon gains. The 2000-2007 period showed a high rate of land clearing: 5.9% of NW Argentina (1,757,600. ha) was cleared for agriculture and ranching, corresponding to an annual rate of 1.15%. Dry forests experienced the highest rate and humid forests the lowest. Though land clearing for agriculture and ranching had relatively small impacts on total annual ANPP, once deforested, parcels significantly became more seasonal than the natural vegetation replaced. Such increase in seasonality is associated with a reduction of photosynthetic activity during a portion of the year (fallow). Direct consequences of this reduction can be expected on several ecosystem services such as erosion control and water regulation, due to greater exposure of bare soil, and biodiversity, due to the loss or decline in habitat quality and the decrease of green biomass availability for primary consumers during fallow. Land clearing also increased the magnitude of inter-annual differences in C gains, suggesting a greater buffer capacity against climate fluctuations of natural vegetation compared to croplands.